Cat Scratch Disease as a Mimicker of Malignancy. (5th October 2021) - Dhal, Udit; Hicklen, Rachel S; Tarrand, Jeffrey; Kontoyiannis, Dimitrios P
Abstract: Cat scratch disease (CSD) infrequently mimics malignancy. We reviewed 11 such cases at MD Anderson Cancer Center and an additional 36 reported from the literature. Breast cancer, sarcoma, and lymphoma were the most commonly suspected malignancies. Most patients were young, female, had prior cat exposure, and had no systemic symptoms. Regional lymphadenopathy was the most common finding.